Simi 2018 2018
DOI: 10.21698/simi.2018.fp03
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Wood Density and Biomass: A Case Study of Forest Plantations From Moldova Noua Waste Heaps, Romania

Abstract: The present paper emphasizes the possibility of using wood from the plantations installed on waste heaps by analysing the density of wood mass and establishing the biomass of species planted on the waste heaps from Moldova Noua. In order to determine wood biomass for the analysed species, wood samples were gathered from a specific sample area. As such, their volume and mass were established both before and after drying them in a stove at a temperature of 105 degrees Celsius for 24 hours. The plantations biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Regarding base saturation degree, the values for the phaeozem in the Dobrogea Plateau (figure 4) confirm that it is an eubazic soil and its values are closer to those of phaeozems in other plains [9][10][11] (table 2).…”
Section: Base Saturation Degree (V)mentioning
confidence: 54%
See 1 more Smart Citation
“…Regarding base saturation degree, the values for the phaeozem in the Dobrogea Plateau (figure 4) confirm that it is an eubazic soil and its values are closer to those of phaeozems in other plains [9][10][11] (table 2).…”
Section: Base Saturation Degree (V)mentioning
confidence: 54%
“…Analyzing the values of the other types of soils (Table 2) it was found that the values of the first horizon Ao of the eutric cambisol, preluvisol and luvisol are higher than the values of the same soils in other parts of the country [9][10][11]. Total cationic exchange capacity (T) If the total cationic exchange capacity is analyzed then the three soil types with the values between 15 and 25 miliequivalents per 100 grams of soil, respectively eutric cambisol, luvisol and preluvisol have a high total cationic exchange capacity and chermozem and phaeozem have a very high values of total cationic exchange capacity with values exceeding 25 miliequivalents per 100 grams of soil (table 3 and figure 5).…”
Section: Base Saturation Degree (V)mentioning
confidence: 99%
“…Flotation waste heaps (also known as decantation ponds), a result of storing material derived from the flotation process represent anthropic field surfaces in which vegetation development is hard due to sterile instability. This instability is accentuated in the case of Moldova Nouă by winds characteristic to this area [11]. Dust pollution in Moldova Nouă is a result of these surfaces and of the strong wind, and has negative effects even on the other side of the Danube.…”
Section: Introductionmentioning
confidence: 93%